APLIKASI PSIKOLINGUISTIK MEMBACA DAN PENGAJARAN BAHASA - Ikawati, Erna (AIN Padangsidimpuan, 2014)
Reading is one of langnege skills that reguire cognitive maturity. Marger methocl of learnig to red between the bottom-up with a top-down is done to get the maximum results. Therefore, psycholinguistics was iastrumental in the planning of language teaching. Implications for tea Cher tooked at the teacter’s ability to manage the teaching, mhether related to the use of the curriculum as wel as in the selection of language materials.